2022
DOI: 10.1029/2021ms002761
|View full text |Cite
|
Sign up to set email alerts
|

One Stomatal Model to Rule Them All? Toward Improved Representation of Carbon and Water Exchange in Global Models

Abstract: Stomatal conductance schemes that optimize with respect to photosynthetic and hydraulic functions have been proposed to address biases in land‐surface model (LSM) simulations during drought. However, systematic evaluations of both optimality‐based and alternative empirical formulations for coupling carbon and water fluxes are lacking. Here, we embed 12 empirical and optimization approaches within a LSM framework. We use theoretical model experiments to explore parameter identifiability and understand how model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 148 publications
(215 reference statements)
1
40
1
Order By: Relevance
“…This study builds upon the work of Bassiouni and Vico (2021) by implementing stomatal models within multi-layer canopy (and big-leaf) ecosystem models and solving optimization routines numerically. The findings of both studies agree; more mechanistic representations of plant hydraulic functioning did not substantially improve predictive or functional accuracy, although other studies have found contrasting results (e.g., Eller et al, 2020;Sabot et al, 2020Sabot et al, , 2022. Our results indicate that hydraulic-modified semi-empirical models, in particular MED-H, can be effectively adapted to incorporate hydraulic constraints based on measurable plant traits.…”
Section: Information Flowssupporting
confidence: 83%
See 1 more Smart Citation
“…This study builds upon the work of Bassiouni and Vico (2021) by implementing stomatal models within multi-layer canopy (and big-leaf) ecosystem models and solving optimization routines numerically. The findings of both studies agree; more mechanistic representations of plant hydraulic functioning did not substantially improve predictive or functional accuracy, although other studies have found contrasting results (e.g., Eller et al, 2020;Sabot et al, 2020Sabot et al, , 2022. Our results indicate that hydraulic-modified semi-empirical models, in particular MED-H, can be effectively adapted to incorporate hydraulic constraints based on measurable plant traits.…”
Section: Information Flowssupporting
confidence: 83%
“…Optimization theory supports the conceptual framework of hydraulic limitation on gas exchange since the cost of hydraulic damage can be incorporated into the cost of water loss. Although there is still much discussion about how hydraulic functioning should be applied in semi‐empirical models (Lin et al., 2015), hydraulic limitations have been incorporated into semi‐empirical stomatal models (Kennedy et al., 2019; Sabot et al., 2022; Tuzet et al., 2003; Wolf et al., 2016; Xu et al., 2016; Yang et al., 2019; Zhou et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Capturing the correct stomatal sensitivity as vapour pressure deficit increases is emerging as a key knowledge gap across models, particularly at high vapour pressure deficit (Yang et al, 2019). Sabot et al (2022) demonstrated wide variability in the sensitivity of stomatal conductance to vapour pressure deficit across the latest generation of optimal stomatal models (Wolf et al, 2016;Sperry et al, 2017;Dewar et al, 2018;Eller et al, 2018). However, as the sensitivity to vapour pressure deficit emerges from the parameterisation of the hydraulic vulnerability curve and the optimisation target, this uncertainty cannot be easily constrained with observations.…”
Section: Identifying How Drought Risk Varies Across Species Rangesmentioning
confidence: 99%
“…Capturing the correct stomatal sensitivity as vapour pressure deficit increases is emerging as a key knowledge gap across models, particularly at high vapour pressure deficit (Yang et al, 2019). Sabot et al (2022) demonstrated wide variability in the sensitivity of stomatal conductance to vapour pressure deficit across the latest generation of optimal stomatal models (Wolf et al, 2016;Sperry et al, 2017;Dewar et al, 2018;Eller et al, 2018). However, as the sensitivity to vapour pressure deficit emerges from the parameterisation of the hydraulic vulnerability curve and the optimisation target, this uncertainty cannot be easily constrained with observations.…”
Section: Identifying How Drought Risk Varies Across Species Rangesmentioning
confidence: 99%